Sikap Uni Eropa Terhadap Konflik Rusia dan Ukraina - Martin, Ali; Farizi, Salman Al (Faculty of Social and Political Sciences - Universitas Wahid Hasyim, 2024)
The attitude of the European Union in the conflict over Russia's invasion of Ukraine which occurred on February 24 2022 has had a major impact on security stability in the European region. So the European Union as a region is experiencing impacts in the form of damage to the ecosystem, social order and humanity due to Russia's invasion of Ukraine. Therefore, providing economic sanctions to reduce Russia's costs in invading Ukraine. This effort is only to maintain the stability of the European region. And the European Union also provides military assistance to Ukraine, even assistance in the form of health and safety to Ukrainian citizens. This is the European Union's stance to reduce the costs of encroaching on Russia and also reduce the burden on Ukraine as an eastern region of Europe. This research was carried out using qualitative methods, meaning that the research mostly uses qualitative data such as values (norms), attitudes, ideologies or people's thoughts which are processed by connecting one phenomenon with another. Specifically, to understand the phenomenon of the European Union's attitude towards the conflict between Russia and Ukraine, data analysis uses interpretive methods. Keywords: European Union Attitude, Invasion, Russia, and Ukraine. ABSTRAK Sikap Uni Eropa dalam konflik invasi Rusia ke Ukraina terjadi pada tanggal 24 Februarai 2022 sangat berdampak pada stabilitas keamanan di kawasan Eropa. Sehingga Uni Eropa sebagai organisasi regional yang mengalami dampak berupa kerusakan ekosistem, tatanan sosial dan juga kemanusiaan atas invasi Rusia ke Ukraina. Maka alternatifnya memberikan sanksi ekonomi agar mengurangi biaya Rusia dalam invasi terhadap Ukraina. upaya tersebut hanya untuk menjaga stabilitas wilayah Eropa. Dan Uni Eropa juga memberikan bantuan militer terhadap Ukraina, bahkan bantunan berupa kesehatan dan keselamatan kepada warga Ukraina Bentuk sikap Uni Eropa untuk mengurangi biaya pengeluaran Rusia dan juga mengurangi beban Ukraina sabagai wilayah timur Eropa. Penelitian ini dilakukan dengan metode diskriptif kualitatif, yang lebih banyak menenkankan pada data kualitatif seperti nilai (norm), sikap, ideologi atau pemikiran orang diproses dengan menghubungkan fenomena yang satu dengan lainnya. Secara khusus untuk memahami fenomena hubungan sikap Uni Eropa terhadap dalam konflik Rusia dan Ukraina, analisis data menggunakan interpretatif